Pendekatan Nature-Based Learning dalam Perancangan Fasilitas Anak Usia Dini di Kota Denpasar: Bahasa Indonesia - Ni Nyoman Ayu Sriwini; Nyoman Ratih Prabandari; I Wayan Parwata; Tjokorda Gede Dalem Suparsa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
Early childhood is a critical phase of development that is strongly influenced by the quality of learning and play environments. In Denpasar City, high child density, limited green open spaces, and increasing screen time highlight the need for alternative child-friendly and nature-oriented learning facilities. This study aims to plan and design a Children’s Nature Learning Hub as a non-formal, community-based learning facility using a nature- based learning approach. The research applies descriptive qualitative method through field observation, literature review, precedent studies, and design synthesis analysis. The nature-based learning approach is implemented through the concept of Learning Through Nature and Play, which integrates play activities, exploration, and sensory experiences into early childhood learning processes. This approach is applied to both outdoor and indoor spatial arrangements, supported by a biophilic architectural theme through flexible spatial design, indoor– outdoor connectivity, vegetation integration, natural materials, daylighting, and natural ventilation. The proposed design is expected to offer an alternative early childhood learning environment that supports holistic development and aligns with the objectives of the Child-Friendly City program in Denpasar.